CHANGES IN THE STABILITY AND POTENTIAL OF CELL SUSPENSIONS : I. THE STABILITY AND POTENTIAL OF BACTERIUM COLI. - Eggerth, Arnold H. (The Rockefeller University Press, 1923)
1. Stability and potential of Bacterium coli suspensions depend, not only on the strain of the organism and the medium in which it is suspended, but also on the previous treatment of the suspension, and the length of time it has been in the medium. 2. When treated at acid reactions, the negative charge on the bacteria is diminished; with some strains, a positive charge is acquired. Changes in stability accompany the changes in potential. 3. Washing acid-treated bacteria at neutral or slightly alkaline reactions does not restore the original potential; the zone of flocculation is moved toward the alkaline side. 4. These changes are due to two factors: the extraction of a soluble protein which combines with the surfaces of the cells, and a further irreversible change of the cell or its membrane.